Mitigation of Elephant Disturbance in Pemerihan Village, Bengkunat Sub-District, Pesisir Barat District - Ardiansyah Ardiansyah; Irma Lusi Nugraheni (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2023)
This study aims to describe the mitigation of elephant disturbance in Pemerihan Village, Bengkunat District, and West Coast District. The population in this study were all people who experienced disturbance by elephants in Pemerihan Village, Bengkunat District. The sample in this study was 52 families using a purposive sampling technique. Retrieval of data using questionnaires, observation, interviews, and documentation techniques. Data analysis using the Likert analysis technique. The results of the elephant disturbance mitigation research in Pemerihan Village are in a physical form by making guard towers, using below lights or large flashlights, and shooting firecrackers. Mitigation of elephant disturbance in the form of biology is carried out by making noise to drive the elephants away, keeping honey bees or bees ringing on the paths that are passed by elephants, and with the ERU (Elephant Responsive Unit). Mitigation of elephant disturbance in a social form is carried out by using tools that are used together to drive away elephants, forming a special task force (task force) to drive elephants into plantations and guarding plantation crops, using various sound devices such as spirit cannons and firecrackers.